FENOMENA INTERAKSI PEREMPUAN DI MEDIA SOSIAL DALAM PERSPEKTIF HUKUM ISLAM - Akhmad Rudi Maswanto (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Questioning women's behavior is actually not an easy task for the author, there is a moral burden where it seems that when women are positioned as research objects, there will be a stigma that men are "pretentious" and more appropriate to judge women. So rest assured that in this study, there is absolutely no gender bias in it, just want to see how the tendency of women in this digital era to interact on social media, this will be associated with family resilience, especially with regard to the assumption of the community that the many problems in the household are the source of the phenomenon or behavior of women's interaction on social media. Through qualitative research, this problem will be identified for every existing problem, so that it is intended to see whether it is true that women's lives on social media are suspected to be the cause of the collapse of household buildings, and how Islam actually regulates the pattern of women's interaction patterns in life outside.